Model Internalisasi Religiusitas dalam Kelurga Buruh Tani Bawang Merah di Kabupaten Probolinggo - Muttaqin, Zaenal (Proceedings of Annual Conference for Muslim Scholars, 2019)
The problem that underlies this research is the problem of the children of farmworkers who do not receive the attention of religious education from their parents so that many children are less expected of the development of their religion. In Sumberbulu Village, Tegalsiwalan Subdistrict, Probolinggo Regency is known for rice fields planted with shallots. The majority of the population work as agricultural laborers. Not only men, many women also work in the profession as farm laborers. This research is a type of qualitative research through a naturalistic approach. In the process of collecting data, researchers used the method of observation, interviews, and documentation. From the results of the study, it can be concluded that based on the results of research and discussion of the model of Islamic education in children of farmers in Sumberbulu Village, Tegalsiwalan District, Probolinggo, the conclusion is: (1) applied by parents is flexible and exemplary from parents sometimes uses a slightly firm manner in accordance with the situation and condition; and (2) the problem of parents in educating their children in the family is the busyness of parents at work, lack of time to gather, and they will in the child himself. While the efforts made by parents are always trying to minimize the existing problems and the willingness of parents to make their children sholih and sholihah children. Families who always try their utmost help in educating and caring for children.